2005
DOI: 10.1128/jcm.43.2.898-902.2005
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Escherichia coli O157 Isolates on Bovine Farms in England and Wales

Abstract: We performed pulsed-field gel electrophoresis on Escherichia coli O157 isolates (n ‫؍‬ 318) from 199 healthy animals in a longitudinal study carried out on nine farms. Investigation of the restriction types proved that at the farm level, the same clones can be detected on sampling occasions separated by as much as 17 months. The cohort animals were repeatedly sampled, and for some of these, the same clones were obtained on sampling occasions separated by as much as 8 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Unfortunately, these cow-calf herds appear to experience seemingly unpredictable sporadic new infections from either an undiscovered environmental point source or from events of high interanimal transmission of an endemic pathogenic strain of E. coli O157:H7 that amplify the environmental food safety risks from the herd. This pattern of variable persistence of specific strains of pathogenic E. coli O157:H7 has been observed in numerous prior studies both in the United States and internationally (27,45,46). Although we found several factors associated with the odds of fecal shedding of these strains of E. coli O157:H7 among California beef cattle, it is unclear whether the shift in season, the changes to the herd density, the length of the calving season, or recent access to surface sources of drinking water can explain these upward spikes in the point prevalence of cattle infection and subsequent fecal shedding.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Unfortunately, these cow-calf herds appear to experience seemingly unpredictable sporadic new infections from either an undiscovered environmental point source or from events of high interanimal transmission of an endemic pathogenic strain of E. coli O157:H7 that amplify the environmental food safety risks from the herd. This pattern of variable persistence of specific strains of pathogenic E. coli O157:H7 has been observed in numerous prior studies both in the United States and internationally (27,45,46). Although we found several factors associated with the odds of fecal shedding of these strains of E. coli O157:H7 among California beef cattle, it is unclear whether the shift in season, the changes to the herd density, the length of the calving season, or recent access to surface sources of drinking water can explain these upward spikes in the point prevalence of cattle infection and subsequent fecal shedding.…”
Section: Discussionsupporting
confidence: 74%
“…The persistence of individual strains within a herd of beef cattle can be weeks to months, with considerable variation observed between previous studies (42)(43)(44)(45)(46). We sought to gain some insight into how the persistence of populations of E. coli O157:H7 might fluctuate over time in California cow-calf herds.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results obtained in this study, the possibility that an identical E. coli or enterococcus clone could be found among isolates from animals within the same farm and between different farms housing the same animal species is 3.4%, and the possibility that an identical E. coli or enterococcus clone can be found among isolates from animals from different farms housing different animal species is 2.0%, as described in RESULTS. Additionally, a study from England has demonstrated that the same E. coli O157 clones can be isolated from the same healthy animal over a period of at least 7 months (Liebana et al, 2005). This suggests that the clonal constitution in the intestines of animals is relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“…coli O157 can persist for an extended period of time on a farm (19,21,28). It is less clear whether the cattle on the farm or the feedlot environment are the reservoir of persistent strains.…”
Section: Discussionmentioning
confidence: 99%